Digital Readiness of Faculty and Students at the State University using Modified General Technology Competency and Use Model with Rule-based Algorithm: Basis for Teaching and Learning Delivery Mode Policy - Fabregas, Aleta; Gapasin, Anna Ruby; Inovero, Carlo; Albano, Gisela May; Canlas, Rosita (International Journal of Computing Sciences Research; Vol 5 (2021): Vol 5, 2020)
Purpose – As an academic institution, the Polytechnic University of the Philippines actively responds to the challenging effect of the COVID 19. One of the actions was to assess its faculty members and students' readiness in adopting digital and virtual worlds as an alternative to the traditional classroom-based learning and teaching method and to come up with appropriate decisions and policies. Method – The Digital Assessing Profiler is an online-based survey to assess the readiness of Faculty and Students in an online-based delivery of teaching. The researchers adopted and modified the General Technology Competency and Use (GTCU) online-learning framework in developing the Digital Assessing Profiler with Rule-Based Algorithm to forecast and to determine the readiness of the students and faculty members in adopting the digital virtual class settings. Results – This study grouped students and faculty into high and low-readiness based on technical, social, informational, and internet dimensions. By applying the rule-based model in the Digital Assessing Profiler, findings show that a large percentage of students are not that prepared for many online-learning activities, and there is generally greater readiness on mobile devices than desktops/laptops. However, large percentages of students appear in high-readiness segments for using social networks and technical and social interactions. Conclusions – The generated assessment on readiness will help the University in crafting relevant policies and guidelines for teaching and learning delivery mode. The researchers recommended the use of a digital assessor profiler which is based on a modified General Technology Competency and Use (GTCU) online-learning framework to align these patterns of strengths with future educational innovation.